The Trotula : an English translation of the medieval compendium of women's medicine - Green, Monica Helen (Philadelphia : University of Pennsylvania Press, 2002)
The Trotula was the most influential compendium on women's medicine in medieval Europe. Green here presents the first modern English translation of the so-called standardized Trotula ensemble, a composite form of the texts that was produced in the mid-thirteenth century and circulated widely in learned circles.
Frontmatter -- Contents -- Nate on the Paperback Edition -- Illustrations -- Preface -- Map -- Introduction -- Book on the Conditions of Women -- On Treatments for Women -- On Women's Cosmetics -- Appendix: Compound Medicines Employed in the Trotula Ensemble -- Notes -- Bibliography -- Index.
Includes bibliographical references (pages 209-220) and index.
Translated from the Latin with introduction and notes in English.
Print version record.
JSTOR
Keywords: Trotula; Gynecology -- Early works to 1800.; Obstetrics -- Early works to 1800.; Women -- Health and hygiene -- Early works to 1800.; Medicine -- Italy -- Salerno -- History; Medicine, Medieval; History, Medieval; Gynécologie -- Ouvrages avant 1800.; Obstétrique -- Ouvrages avant 1800.; Médecine -- Italie -- Salerne -- Histoire; Médecine médiévale.; LITERARY COLLECTIONS -- Ancient & Classical; Gynecology; Medicine; Medicine, Medieval; Obstetrics; Women -- Health and hygiene; Italy -- Salerno; Vrouwen; Gynaecologie; Verloskunde; Caregiving; Gender Studies; Health; History; Medicine; Medieval and Renaissance Studies; Women's Studies; Early works; History